Case Report: One-Year Delay in the Effect of Conversion Surgery Therapy for Advanced Hepatocellular Carcinoma After Systemic Therapy - Xie, Qing-Yu; Liu, Hai-Yan; Guo, Ze-Yi; Wu, Yan-Ping; He, Guo-Lin; Cai, Lei; Pan, Ming-Xin; Fu, Shun-Jun (Frontiers in Molecular Biosciences, 2022)
Hepatocellular carcinoma (HCC) is the sixth most commonly diagnosed malignancy and the third leading cause of cancer-related deaths worldwide. A 58-year-old man visited his local hospital due to abdominal discomfort and was diagnosed with lung metastasis. After admission to our hospital in April 2020, he received two cycles of transcatheter arterial embolization (TAE), hepatic arterial infusion chemotherapy (HAIC-Folfox), sorafenib, and camrelizumab every 3 weeks. Due to the end of HAIC treatment, he underwent drug-eluting transcatheter arterial chemoembolization (dTACE) once, sorafenib, and camrelizumab. However, because of worsening liver function, we interrupted TACE and only gave sorafenib and camrelizumab in August 2020. Although he received systemic therapy, the tumors still rapidly progressed and we considered the possibility of tumor resistance. Subsequently, regorafenib was given. In September, the patient underwent conventional TACE (cTACE) once, regorafenib, and camrelizumab. After half a year of comprehensive treatment, the treatment effect was not satisfactory, and he returned to the local hospital to received regorafenib every day and camrelizumab once every 3 weeks. The patient found that the tumor and lung metastasis had shrunk significantly after 1 year of the initial diagnosis, then he was admitted to our hospital and received surgery treatment, and now he has survived disease-free for 6 months.